Reappearance of limbal pigmentation post-simple limbal epithelial transplant - Gupta, Nidhi (Indian J Ophthalmol, 2020)
We report the repigmentation at the limbus in patients who underwent simple limbal epithelial transplant (SLET) for uniocular chemical injury. The first case is of an 8-year-old child who presented with grade 4 chemical injury, with limbal stem cell deficiency (LSCD) corresponding to 6 o' clock till 11 o' clock. He was managed by amniotic membrane graft in the acute stage and SLET after 6 months of the initial injury. The second case is of a 15-year-old female who presented with lime injury, which had resulted in 6 o' clock of limbal involvement (10 o' clock till 4 o' clock). The patient was managed on similar lines with amniotic membrane graft (AMG) in the acute phase and SLET after 6 months of injury. The ocular surface was stable in both the patients post-SLET. The effected limbus showed pigmentation at 8 months of follow-up which eventually became distinct and remained stable. We speculate that the pigmentation at limbus could be attributed to proliferation and movement of melanocytes from limbal biopsy in SLET. These may be capable of supporting the proliferation of limbal epithelial cells and modulation of corneal wound healing.